Blockchain Technology in Scientific Data Management: ‎Security and Efficiency Perspectives - Praveen , K. N. Raja; Bhanot , Deepak; Sidhu , Amritpal; Agarwal , Dr. Trapty; Patil , Dr. Shashikant; Jena , Sanjay Kumar; Lakshmanan , Dr.L. (International Journal of Basic and Applied Sciences, 2025)
Blockchain is a decentralized architectural model that creates an immutable ledger in a distributed manner for recording all  ‎transactions. Typically, blockchain is a protected and decentralized data store where all the records are positioned in order, as well as events ‎called blocks. All types of data that are apparent to the nodes are recorded in the blockchain-driven system. Meanwhile, it is the apparent, ‎distributed, and open ledger that effectively records every transaction between two parties in an enduring and verifiable way. Once the ‎information is stored, the information present in the blockchain does not get changed unless a record is inserted. In cryptocurrencies, each ‎user has a precise ledger in the network domain, ensuring the complete agreement of users or nodes in the blockchain currencies. The ‎characteristics of blockchain, including transparency, security, and immutability, facilitate the recording and verification of transactions, ‎rendering it appropriate for secure document management, identity verification, maintaining record integrity, and obviating the necessity for ‎third-party intermediaries in transaction verification. The blockchain-based access control technique was devised to enhance security. ‎Consequently, the access control management system stipulates that the total characteristics must be inferior to the number of users‎.
Keywords: Blockchain; Data Management; Security and Efficiency